Combination of glycin and thiotriazolin in a single medicinal form - O. V. Khromylova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The beginning of this millennium was marked by significant spread of cardiovascular disease, which took 1–2 place in the mortality structure of industrialized countries. Certain interest is paid to glycine, as a promising primary neuroprotector. It provides the normal functioning of NMDA receptors, due to its effect on glycine sites, which has a metabolitotropic and energotropic effect. There is evidence of the ability of anti-oxidant thiotriazoline to potentiate the therapeutic effect of neuro-metabolic cerebroprotectors. Therefore, it is interesting to create a new combined drug based on glycine and thiotriazoline.